1996
DOI: 10.1093/bja/76.3.461
|View full text |Cite
|
Sign up to set email alerts
|

Fentanyl increases intracellular Ca2+ concentrations in SH-SY5Y cells

Abstract: Classically, opioids inhibit Ca2+ influx, but recent reports suggest opioids may also stimulate Ca2+ entry. Therefore, we have measured the effect of opioids on intracellular Ca2+ ([Ca2+]i), fluorimetrically, in Fura-2-loaded SH-SY5Y cells. Fentanyl 0.3 mumol litre-1 caused a mean increase in [Ca2+]i of 18.8 (SEM 2.1) nmol litre-1 in some (30.3%) batches of SH-SY5Y cells. In responding cells, the fentanyl-induced increase in [Ca2+]i was dose-dependent, with an EC50 of 0.73 mumol litre-1. This response was nalo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 5 publications
2
9
0
Order By: Relevance
“…Control experiments revealed that SH‐SY5Y cells produced an increase in [Ca 2+ ] i in response to the muscarinic receptor agonist carbachol (1 m M ). These data are consistent with our previous findings (Wandless et al ., 1996).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Control experiments revealed that SH‐SY5Y cells produced an increase in [Ca 2+ ] i in response to the muscarinic receptor agonist carbachol (1 m M ). These data are consistent with our previous findings (Wandless et al ., 1996).…”
Section: Resultsmentioning
confidence: 96%
“…However we have previously shown that in SH‐SY5Y cells PLC activation is dependent upon Ca 2+ entry (Smart et al ., 1995). The subsequent Ins(1,4,5)P 3 formation does not appear to be sufficient to cause an increase in Ca 2+ , although μ‐opioid receptor activation in the same cells causes a small and unpredictable increase in [Ca 2+ ] i with very high concentrations of fentanyl (Wandless et al ., 1996), which may be due to calcium entry. Other studies have found that ‘priming’ of SH‐SY5Y cells with the muscarinic agonist carbachol is necessary to produce an opioid mediated increase in [Ca 2+ ] i (Connor & Henderson, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Although morphine induced less pCREB formation after cellular depletion of PKC by PMA pretreatment, this increase was abolished by KN62, arguing for a role of both PKC and CaMKs. In SH‐SY5Y cells, opioid receptor stimulation leads to activation of PKC (Smart et al, 1995; Wandless et al, 1996). Whether PKC plays a direct role in CREB phosphorylation remains to be seen.…”
Section: Discussionmentioning
confidence: 99%
“…These signaling pathways suppress neuronal excitability; however, opioid receptors also trigger various poorly defined signaling pathways that can stimulate cellular activity. For example, opioid receptors have been shown to enhance Ca 2+ influx/release (Smart et al, 1995; Wandless et al, 1996; Thorlin et al, 1998; Lin et al, 1999) and to activate mitogen‐activated protein kinase (MAPK) (Fukuda et al, 1996; Hawes et al, 1998) via G i /G o proteins.…”
mentioning
confidence: 99%
“…Endogenous μ‐opioid receptors in SH‐SY5Y human neu‐roblastoma cells also inhibit N‐type VSCCs (Seward et al , 1991), as well as basal and forskolin‐stimulated cyclicAMP formation (Lambert et al , 1993; Smart et al , 1995a). Furthermore, the μ‐opioid receptor also stimulates Ins(1,4,5)P 3 formation in these cells (Smart et al , 1994; 1995a), by opening L‐type VSCCs (Smart & Lambert, 1995; Smart et al , 1995a) via a pertussis toxin (PTX)‐sensitive G‐protein (Smart et al , 1994), and so allowing Ca 2+ influx (Wandless et al , 1996) which activates PLC.…”
Section: Introductionmentioning
confidence: 99%